James' Place model: application of a novel clinical, community-based intervention for the prevention of suicide among men. Issue 1 (21st January 2022) - Hanlon, Claire Anne; Chopra, Jennifer; Boland, Jane; McIlroy, David; Poole, Helen; Saini, Pooja
Abstract : Purpose: High suicide rates among men presents a global challenge for commissioners and clinicians. Innovative approaches towards suicide prevention interventions designed for men are needed. The James' Place (JP) service opened in 2018, and its model of practice is a clinical, community-based intervention for men experiencing suicidal crisis. This paper aims to describe the implementation framework within which the JP model is applied. Design/methodology/approach: Fostering a public health case study approach, this paper provides a description of how the JP service operates, including the referral pathways, key components of this innovative model and its impact upon the men who receive the intervention. Illustrative case studies derived from semi-structured interviews from men and therapists are reported. Findings: The JP model is dynamic and flexible, allowing the tailoring of a suicidal crisis intervention to suit the needs and priorities of the individual and the wider local community. Clinical and practical implications, such as reduction in suicidality, are discussed. Originality/value: Rapidly accessible, effective community-based interventions for men experiencing suicidal crisis are required. Yet, while widely advocated in policy, there remains a dearth of evidence illustrating the real-world application and value of such services within a community-setting. To the best of the authors' knowledge, the JP model is the first of its kind in the UK and an example of an innovative clinical, community-based suicide prevention intervention offering support for men experiencing suicidal crisis.